Using Remote Lab for Enhancing E-Learning on FPAAs - Felgueiras, Manuel Carlos (2017)
Analog and digital electronic subjects are part of the electronic engineer degree but its taught is not easy because they are founded in opposite methodologies. The electronic design in the digital field is centered in the use of microprocessor and FPGA based circuits using high level programing/configuring languages. The counterpart analog design is traditionally based in the use of elementary com- ponents associated with macroblocks such operational am- plifiers in order to built-up the wanted mission circuit. Some few components, as the FPAA, are analogically configurable in a similar manner already used with the FPGA. However the use of this kind of components is not straightforward once is necessary acquire some concepts not taught in the traditionally analog electronic classes. The current work present an innovative remote lab to sup- port teaching of the FPAAs.